The Influence of Campus Ecological Environment on Student Ecological Citizenship: ANCOVA's Nonparametric Quade Analysis in Three Cities in Indonesia - Minto Santoso; Isyanto; Suhartono; Siti Aisyah (Universitas Negeri Surabaya, 2026)
This study aims to analyze the influence of campus ecological environmental conditions on students' ecological citizenship and test the differences between regions in three cities, namely Blitar, Sumenep, and Surabaya. The method used is a comparative quantitative approach with an ex post facto design. Data were collected through questionnaires of 190 college students and analyzed using ANCOVA's Nonparametric Quade to control for covariate variables under unnormally distributed data conditions. The results of the study show that the ecological environment condition of the campus has a significant effect on the ecological citizenship of students contribution of 47.9%. However, after covariate control, there was no significant difference in the level of ecological citizenship between cities. In addition, the influence of the campus ecological environment has proven to be consistent across various regional contexts. ANCOVA's Quade Nonparametric approach also shows that ranking adjustments result in more stable estimates in the analysis of nonparametric data. The conclusion of this study confirms that the ecological environment of the campus is the main factor in forming student ecological citizenship, while geographical factors do not show a significant role after being controlled. This research makes an empirical and methodological contribution to the study of sustainability education in higher education.